Placental ESRRG-CYP19A1 Expressions and Circulating 17-Beta Estradiol in IUGR Pregnancies - Gaia Maria Anelli; Chiara Mandò; Teresa Letizia; Martina Ilaria Mazzocco; Chiara Novielli; Fabrizia Lisso; Carlo Personeni; Tarcisio Vago; Irene Cetin; Irene Cetin (Frontiers Media S.A., 2019)
Introduction: Sex steroids are regulating factors for intrauterine growth. 17-β Estradiol (E2) is particularly critical to a physiological pregnancy, as increased maternal E2 was correlated to lower fetal weight at delivery. The placenta itself is a primary source of estrogens, synthetized from cholesterol precursors. Cytochrome P450 aromatase (encoded by CYP19A1 gene) is a rate-limiting enzyme for E2 biosynthesis. CYP19A1 transcription is supported by Estrogen Related-Receptor Gamma (ERRγ- ESRRG gene), which thus has an indirect role in placental steroidogenesis. Here we investigated maternal E2 levels and placental CYP19A1 and ESRRG expressions in pregnancies with IntraUterine Growth Restriction (IUGR).Methods: Singleton pregnancies were studied. E2 was measured in maternal plasma by electrochemiluminescence in 16 term controls and 11 IUGR (classified by umbilical artery doppler pulsatility index) at elective cesarean section, and also in 13 controls during pregnancy at a gestational age comparable to IUGR. CYP19A1 and ESRRG expressions were analyzed in placental tissue. Maternal/fetal characteristics, placental and molecular data were compared among study groups and tested for correlations.Results: Maternal E2 plasma concentrations were significantly decreased in IUGR compared to controls at delivery. When analyzing normal pregnancies at a gestational age similar to IUGR, E2 levels were not different to pathological cases. However, E2 levels at delivery positively correlated with placental efficiency. Placental CYP19A1 levels were significantly higher in IUGR placental tissue vs. controls, and specifically increased in female IUGR placentas. ESRRG expression was not different among groups.Discussion: We report a positive correlation between 17-β Estradiol levels and placental efficiency, that might indicate a disrupted steroidogenesis in IUGR pregnancies. Moreover, we show alterations of CYP19A1 expression in IUGR placentas, possibly indicating a compensatory effect to the adverse IUGR intrauterine environment, also depending on fetal sex. Further studies are needed to deeper investigate IUGR alterations in the complex interaction among molecules involved in placental steroidogenesis.